Al-Dirāsah al-Muqāranah baina Kitābay al-Jurūmiyah al-Jawān wa Matn Alajrūmiyah fī al-Bāb Marfū’at al-Asmā’ - Revi Fradita; Muhamad Agus Mushodiq; Nailul Izzah (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2024)
Arabic without the knowledge of Ilm Nahwu cannot be understood. The Matn Alajrūmiyah and al-Jurumiyah al-Jawan are reference books for learning qawāid (Arabic grammar), commonly used in Islamic boarding school environments. All students must study Arabic grammar as a basis for their ability to read the manuscript (turāś). This research aims to explain the differences in the preparation of qawāid learning materials, especially in the Marfūat al-Asmā' chapter in the al-Jurumiyah al-Jawan book and the Matn Alajrūmiyah book so that students can detect the ease of learning Arabic using these two books. The type of research used is qualitative library research with comparative study methods. The results of the research show that both books have complete material regarding Marfūat al-Asmā' along with relevant examples. The difference lies in the additional content, where the author of the al-Jurumiyah al-Jawan book not only presents material on Arabic language rules but also inserts ancestral advice. As for the book Matn Alajrūmiyah, the author only focuses on the rules of Marfūat al-Asmā'. al-Jurumiyah al-Jawan uses the Arabic pegon script with Javanese as the language of instruction, except in examples. The Matn Alajrūmiyah uses Arabic script and Arabic as a whole. As for the style of presentation, the al-Jurumiyah al-Jawan book uses a poetry style that is relatively easy to memorize, in contrast to the Matn Alajrūmiyah, which uses a prose style.